Comparative investigations in the effect of angle of attack profile on hydrodynamic performance of bio-inspired foil, (corrected) (Journal of Naval Architecture and Marine Engineering, 2013)
In flapping underwater vehicles the propulsive performance of harmonically sinusoidal heaving and pitching foil will be degraded by some awkward changes in effective angle of attack profile, as the Strouhal number increases. This paper surveys different angle of attack profiles (Sinusoidal, Square, Sawtooth and Cosine) and considers their thrust production ability. In the wide range of Strouhal numbers, thrust production of Square profile is considerable but it has a discontinuity in heave velocity profile, in which an infinite acceleration exists. This problem poses a significant defect in control of flapping foil. A novel profile function is proposed to omit sharp changes in heave velocity and acceleration. Furthermore, an optimum profile is found for different Strouhal numbers with respect to Square angle of attack profile.DOI: http://dx.doi.org/10.3329/jname.v10i2.14229